To solve the system of equations using the elimination method, we start with the given equations:
-
\(3x - 4y = -4\)
-
\(x + 3y = -10\)
First, we will multiply the second equation to align the coefficients of \(x\) or \(y\). We can multiply the second equation by 3:
\[ 3(x + 3y) = 3(-10) \] This gives us:
\[ 3x + 9y = -30 \]
Now, we have the following system of equations:
-
\(3x - 4y = -4\)
-
\(3x + 9y = -30\)
Next, we will subtract the first equation from the second equation to eliminate \(3x\):
\((3x + 9y) - (3x - 4y) = -30 - (-4)\)
This simplifies to:
\[ 9y + 4y = -30 + 4 \] \[ 13y = -26 \] \[ y = -2 \]
Now that we have \(y\), we can substitute it back into one of the original equations to find \(x\). We'll use the second equation:
\[ x + 3(-2) = -10 \] \[ x - 6 = -10 \] \[ x = -10 + 6 \] \[ x = -4 \]
Thus, the solution to the system of equations is:
\((x, y) = (-4, -2)\).
The answer is:
\(\boxed{(-4, -2)}\).